2012
DOI: 10.1007/s00436-012-3210-5
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA level of the galectin-10 of Angiostrongylus cantonensis induced by reactive oxygen stress

Abstract: Galectin plays an important role in host-parasite interactions. In this study, we identified a novel gene encoding galectin-10 (AcGal-10) from the cDNA library of Angiostrongylus cantonensis and characterized its biological role in the parasite. Sequence and phylogeny analysis showed that AcGal-10 is related to other galectin family members with the conserved loci (H(84)-D(86)-R(88)-V(96)-N(98)-W(105)-E(108)-R(110)). The mRNA level of AcGal-10 was expressed in reactive oxygen stress radicals. We have identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the invasion of the central nervous system (CNS) by developing larvae of the parasite can cause eosinophilic inflammation [ 7 9 ]. The larvae generally remain in the CNS and eosinophil recruitment can cause neuropathological damage [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the invasion of the central nervous system (CNS) by developing larvae of the parasite can cause eosinophilic inflammation [ 7 9 ]. The larvae generally remain in the CNS and eosinophil recruitment can cause neuropathological damage [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reported that soluble antigens derived from stage- IV A.C . larvae contain various proteins that play diverse functions during infection [ 19 , 26 , 45 ]. In our study, sAgs from A.C .…”
Section: Discussionmentioning
confidence: 99%
“…As no function has yet been attributed to parasite galectins, it has been speculated that they may be involved in host–parasite interaction . For example, a galectin from Angiostronglylus cantonensis plays a role in the activation of microglia, but the mechanism is unknown . Moreover, current evidence suggests that parasite galectins participate actively in the infection process as pattern‐recognition receptors (PRRs) .…”
Section: Discussionmentioning
confidence: 99%